Complete Versus Culprit-Only Revascularization in Older Patients With ST-Segment-Elevation Myocardial Infarction: An Individual Patient Meta-Analysis - Campo, Gianluca; Böhm, Felix; Engstrøm, Thomas; Smits, Pieter C; Elgendy, Islam Y; McCann, Gerry P; Wood, David A; Serenelli, Matteo; James, Stefan; Høfsten, Dan Eik; Boxm-de Klerk, Bianca M; Banning, Adrian; et al. (Circulation (New York, N.Y.), 2024)
BACKGROUND: Complete revascularization is the standard treatment for patients with ST-segment-elevation myocardial infarction and multivessel disease. The FIRE trial (Functional Assessment in Elderly Myocardial Infarction Patients With Multivessel Disease) confirmed the benefit of complete revascularization in a population of older patients, but the follow-up is limited to 1 year. Therefore, the long-term benefit (>1 year) of this strategy in older patients is debated. To address this, an individual patient data meta-analysis was conducted in patients with ST-segment-elevation myocardial infarction ≥75 years of age enrolled in randomized clinical trials investigating complete versus culprit-only revascularization strategies. METHODS: PubMed, Embase, and the Cochrane database were systematically searched to identify randomized clinical trials comparing complete versus culprit-only revascularization. Individual patient-level data were collected from the relevant trials. The primary end point was death, myocardial infarction, or ischemia-driven revascularization. The secondary end point was cardiovascular death or myocardial infarction. RESULTS: Data from 7 randomized clinical trials encompassing 1733 patients (917 randomized to culprit-only and 816 to complete revascularization) were analyzed. The median age was 79 [interquartile range, 77-83] years. Of the patients, 595 (34%) were female. Follow-up ranged from a minimum of 6 months to a maximum of 6.2 years (median, 2.5 [interquartile range, 1-3.8] years). Complete revascularization reduced the primary end point up to 4 years (hazard ratio, 0.78 [95% CI, 0.63-0.96]) but not at the longest available follow-up (hazard ratio, 0.83 [95% CI, 0.69-1.01]). Complete revascularization significantly reduced the occurrence of cardiovascular death or myocardial infarction at the longest available follow-up (hazard ratio, 0.76 [95% CI, 0.58-0.99]). This was observed even when censoring the follow-up at each year. Long-term rate of death did not differ between complete and culprit-only revascularization arms. CONCLUSIONS: In this individual patient data meta-analysis of older patients with ST-segment-elevation myocardial infarction and multivessel disease, complete revascularization reduced the primary end point of death, myocardial infarction, or ischemia-driven revascularization up to 4 years. At the longest follow-up, complete revascularization reduced the composite of cardiovascular death or myocardial infarction but not the primary end point. REGISTRATION: URL: https://www.crd.york.ac.uk/prospero/; Unique identifier: CRD42022367898.
Keywords: ST Elevation Myocardial Infarction; Age Factors; mužské pohlaví; Male; senioři; senioři nad 80 let; výsledek terapie; Humans; Female; Myocardial Revascularization; lidé; ženské pohlaví; revaskularizace myokardu; Percutaneous Coronary Intervention; infarkt myokardu s elevacemi ST úseků; koronární angioplastika; Randomized Controlled Trials as Topic; Aged, 80 and over; randomizované kontrolované studie jako téma; Treatment Outcome; Aged; věkové faktory